Positive electrodes for lithium-ion secondary batteries

By employing olivine-type lithium manganese iron phosphate with specific size and stoichiometric adjustments and sulfur doping, the discharge energy and capacity of lithium ion secondary batteries are enhanced, addressing the limitations of high resistivity and conductivity issues.

JP7619008B2Active Publication Date: 2025-01-22TORAY INDUSTRIES INC +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020187845
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-11-11
Publication Date
2025-01-22
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate positive electrode active materials exhibit insufficient discharge energy, particularly under high charging/discharging currents, due to high electrical resistivity and limited electronic and ionic conductivity.

Method used

The positive electrode uses olivine-type lithium manganese iron phosphate with a crystallite size less than 60 nm, a manganese content molar fraction of 0.5 to 1.0, a lithium-to-phosphorus molar ratio of 1.05 to 1.10, and a sulfur content molar fraction of 0.03 to 0.05, along with a carbon coating, to enhance conductivity and capacity.

Benefits of technology

This configuration results in a lithium ion secondary battery with improved discharge energy and capacity, even under high current conditions, by optimizing the crystallite size, stoichiometry, and incorporating sulfur as a doping element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619008000001
    Figure 0007619008000001
Patent Text Reader

Abstract

To provide a positive electrode for a lithium ion secondary battery, having excellent energy characteristics even under conditions with a large charge / discharge current.SOLUTION: A positive electrode for a lithium ion secondary battery contains, as an active material, olivine type lithium manganese iron phosphate containing sulfur elements. The crystallite size of olivine type lithium manganese iron phosphate is less than 60 nm, the mole fraction (Mn content / (Me+Fe) content) of the content of manganese with respect to the total content of manganese and iron is 0.5 or more and less than 1.0, the mole fraction (Li content / P content)of the content of lithium with respect to the content of phosphorus is 1.05 or more and 1.10 or less, and the mole fraction (S content / lithium manganese iron phosphate content) of sulfur in olivine type lithium manganese iron phosphate is 0.03 or more and 0.05 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a lithium ion secondary battery and a lithium ion secondary battery using the same. [Background technology]

[0002] Lithium-ion secondary batteries have high energy density and excellent output characteristics, but if a malfunction occurs, the stored energy is released in a short time, and there is a risk of the battery catching fire or bursting into flames. Therefore, improving safety as well as improving output characteristics is an important issue for lithium-ion secondary batteries.

[0003] It is well known that the safety of lithium-ion secondary batteries is largely determined by the positive electrode active material. The layered rock salt transition metal lithium oxide positive electrode active material, which is often used in large batteries for electric vehicles, etc., is a positive electrode active material that exhibits particularly high energy density, but it has safety issues such as accelerated deterioration due to changes in crystal structure accompanying oxygen release during charging and discharging, which may lead to smoke generation and fire depending on the usage conditions.

[0004] On the other hand, lithium iron phosphate positive electrode active material, which is often used in stationary batteries, does not easily release oxygen because oxygen is covalently bonded to phosphorus, and is a highly safe positive electrode material that is relatively stable even under high temperature conditions. However, its energy density is known to be lower than that of layered rock salt transition metal lithium oxide positive electrode active materials.

[0005] The lithium iron manganese phosphate cathode active material in which part of the iron atoms in lithium iron phosphate are substituted with manganese atoms has the same theoretical discharge capacity (mAh / g) as lithium iron phosphate, but the discharge voltage is improved because the iron atoms are substituted with manganese atoms, so a higher energy density is exhibited than that of the lithium iron phosphate cathode active material. Since the state in which oxygen is covalently bonded to phosphorus remains maintained even when part of the iron atoms are substituted with manganese atoms, the lithium iron manganese phosphate cathode active material has the possibility of achieving both high energy density and high safety. Therefore, it is being considered as a cathode active material to replace the lithium iron phosphate cathode active material. Regarding the lithium iron manganese phosphate cathode active material, for example, an electrode active material characterized by containing sulfur or a sulfur compound in a compound represented by the formula Li x A y B z PO4 (where A is one or more selected from the group of Co, Mn, Ni, Fe, Cu, Cr, B is one or more selected from the group of Mg, Ca, Sr, Ba, Ti, Zn, B, Al, Ga, In, Si, Ge, Sc, Y, rare earth elements, 0 < x < 2, 0 < y < 1.5, 0 ≦ z < 1.5) (see, for example, Patent Document 1), a composite oxide having an olivine structure represented by the chemical formula Li a M x PO4 (0 < a ≦ 1.2, 0.9 ≦ x ≦ 1.1, M is a transition metal containing either Fe or Mn), and the peak intensity ratio (I(020) / I(101)) of (020) and (101) in the X-ray diffraction measurement using the Cu-Kα line of the cathode is 3.5 or more and 4.2 or less (see, for example, Patent Document 2), the empirical formula Li a Mn b Fe c D dA particulate cathode material has been proposed (see, for example, Patent Document 3), which includes an electroactive material having PO4, in which a is a number from 0.85 to 1.15, b is from 0.65 to 0.95, c is from 0.049 to 0.349, d is from 0.001 to 0.1, and 2.75≦(a+2b+2c+dV)≦3.10, in which V is the valence of D, and D is a specific metal ion, and further in which at least a part of the electroactive material has an olivine structure. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-161038 A [Patent Document 2] JP 2011-76820 A [Patent Document 3] JP 2018-60811 A Summary of the Invention [Problem to be solved by the invention]

[0007] Lithium manganese iron phosphate positive electrode active material has a higher energy density than lithium iron phosphate and is less likely to release oxygen than layered oxide positive electrode active material, and is therefore known as a high-performance and safe positive electrode active material. However, lithium manganese iron phosphate, especially a positive electrode active material containing a high proportion of manganese (active material with manganese content / (total content of manganese and iron)≧0.5), has a higher electrical resistivity than lithium iron phosphate by three orders of magnitude or more, making it difficult to obtain a capacity close to the theoretical value expected from the crystal structure, and therefore the energy density is insufficient. According to Patent Documents 1-3, in an olivine positive electrode active material, the electron and ion conductivity of the positive electrode active material is improved by doping with a different element or optimizing the particle size, and the discharge energy is improved when used as a lithium ion secondary battery. However, the electrodes disclosed in Patent Documents 1-3 have a problem of insufficient discharge energy, especially under conditions of large charge and discharge currents.

[0008] In view of the above problems, an object of the present invention is to provide a positive electrode for a lithium ion secondary battery that has excellent energy characteristics even under conditions of large charge / discharge currents. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention mainly has the following configuration. A positive electrode for a lithium ion secondary battery containing an olivine-type lithium manganese iron phosphate containing elemental sulfur as an active material, A positive electrode for a lithium ion secondary battery, wherein the crystallite size of the olivine-type lithium manganese iron phosphate is less than 60 nm, the molar fraction of the manganese content to the total content of manganese and iron (Mn content / (Mn+Fe) content) is 0.5 or more and less than 1.0, the molar ratio of the lithium content to the phosphorus content (Li content / P content) is 1.05 or more and 1.10 or less, and the molar fraction of sulfur in the olivine-type lithium manganese iron phosphate (S content / lithium manganese iron phosphate content) is 0.03 or more and 0.05 or less. Effect of the Invention

[0010] By using the positive electrode for a lithium-ion secondary battery of the present invention, a lithium-ion secondary battery with high discharge energy can be obtained even under conditions where the charge-discharge current is large.

Mode for Carrying Out the Invention

[0011] The positive electrode for a lithium-ion secondary battery of the present invention (hereinafter sometimes simply referred to as "positive electrode") contains lithium manganese iron phosphate (hereinafter sometimes abbreviated as LMFP). As described above, LMFP is excellent in safety and can achieve a higher voltage compared to lithium iron phosphate (hereinafter sometimes abbreviated as LFP), which is a currently used highly safe material. LMFP particles can vary in particle size and the stoichiometry of each element depending on the manufacturing conditions, and can also be doped with elements other than phosphorus, manganese, and iron. However, through the studies of the present inventors, in LMFP, the crystallite size is less than 60 nm, the molar fraction of the manganese content relative to the total content of manganese and iron (Mn content / (Mn + Fe) content) is 0.5 or more and less than 1.0, the molar ratio of the lithium content relative to the phosphorus content (Li content / P content) is 1.05 or more and 1.10 or less, and the molar fraction of sulfur in LMFP (S content / lithium manganese iron phosphate content) is 0.03 or more and 0.05 or less. By doing so, it has been found that the capacity characteristics are improved and the discharge energy increases even under conditions where the charge-discharge current is large.

[0012] LMFP generally refers to a compound in Li α Mn a Fe b PO4 that satisfies 0 < a ≤ 1.1, 0 < b ≤ 1.1, and 0.9 ≤ a + b ≤ 1.1. In the present invention, 1.05 ≤ α ≤ 1.10. However, even when other metal elements are added in the range of 0.1% by weight or more and 10% by weight or less as doping elements, they are also included in the LMFP in the present invention.

[0013] The crystallite size of the LMFP in the present invention is less than 60 nm. LMFP with a high manganese ratio has lower electronic conductivity and ionic conductivity than LFP, so that the battery overvoltage is likely to increase, and the actual capacity and discharge voltage when discharged within a certain voltage range are small, and the discharge energy is likely to decrease. When the crystallite size of LMFP is 60 nm or more, the distance that electrons and lithium ions diffuse within the active material becomes long, so that the capacity decreases significantly relative to the theoretical capacity and the discharge energy decreases. On the other hand, particles with a crystallite size of less than 60 nm have a short diffusion distance within the primary particles of electrons and lithium ions, while the diffusion distance is short, especially in the case of the general formula Li 1.00 Mn 1.00-x Fe x (PO4) 1.00 In the case of a stoichiometric LMFP represented by the formula (1), it was difficult to obtain a discharge capacity close to the theoretical capacity. This is presumably because an LMFP with a small crystallite size has a large specific surface area, and therefore the crystal structure is easily disturbed near the crystal surface. The present inventors have found that in such an LMFP with a small crystallite size, the capacity characteristics are improved and the discharge energy is improved by setting the phosphorus content and sulfur content within the above-mentioned ranges.

[0014] The crystallite size of LMFP can be calculated by performing powder X-ray diffraction measurement on a powder sample of LMFP at a diffraction angle 2θ in the range of 10 degrees to 70 degrees, and performing Rietveld analysis on the obtained diffraction pattern. The powder sample of LMFP can be obtained by grinding the positive electrode mixture peeled off from the positive electrode for lithium ion secondary batteries. In addition, the LMFP powder, which is the raw material for the positive electrode for lithium ion secondary batteries, may be directly measured.

[0015] In the present invention, the molar fraction (a / (a+b)) of the manganese content (a) to the total content (a+b) of manganese and iron in the LMFP is 0.5 or more and less than 1.0. In the LMFP, the larger the manganese ratio a and the smaller the iron ratio b, the smaller the redox couple Mn in the discharge reaction of the battery. 3+ / 2+ The proportion of Fe increases. 3+ / 2+ The redox couple is Li + / Li redox couple, whereas Mn 3+ / 2+ Since the redox couple shows a potential of about 4.1 V, the higher the manganese ratio a, the higher the average discharge voltage of the battery. On the other hand, the theoretical capacity is about 170 mAh / g. Therefore, the higher the manganese ratio a, the higher the theoretical discharge energy.

[0016] In the present invention, the molar ratio α of the lithium content to the phosphorus content of the LMFP particles (Li content / P content) is 1.05 or more and 1.10 or less. As described above, it has been difficult to obtain a discharge capacity close to the theoretical capacity with particles having a crystallite size of less than 60 nm in the past. Therefore, in the present invention, by containing an excess amount of lithium atoms relative to phosphorus, it is possible to achieve a capacity closer to the theoretical capacity and increase the discharge energy. The lithium atoms contained in excess are present in interstitial positions of the LMFP, or are present as a Li3PO4 coating layer on the outer periphery of the LMFP primary particles, or are present as Li3PO4 in the voids between the LMFP primary particles. 、 These are some of the possibilities, but in any case, it is believed that the capacity loss is suppressed by suppressing the disturbance of the crystal structure of the LMFP mentioned above. If the mole fraction α of lithium to phosphorus is less than 1.05, this effect is not obtained and the discharge energy decreases. On the other hand, if the mole fraction α of lithium to phosphorus exceeds 1.10, the excess lithium inhibits the charge and discharge in the positive electrode active material, and the discharge energy decreases.

[0017] In the present invention, the LMFP contains sulfur as a doping element, and the molar fraction α of sulfur in the LMFP (S content / lithium manganese iron phosphate content) is 0.03 or more and 0.05 or less. As described above, LMFP with a high manganese ratio has lower electronic conductivity and ionic conductivity than LFP. Therefore, in addition to making the crystallite size less than 60 nm, it is effective to dope with a different element. The doped sulfur is 、 In LMFP crystals (PO4) 3- (SO4) 2-It is assumed that it exists in the form of being replaced by ( SO4) 2- Substitution by (PO4) 3- Since the difference in charge between the sulfur and the positive electrode supplies conductive carriers, it contributes to improving the electronic conductivity and ionic conductivity of the LMFP primary particles, thereby improving the capacity under conditions of large charge / discharge currents and increasing the discharge energy. If the sulfur molar fraction α is less than 0.03, such effects cannot be obtained and the discharge energy decreases under conditions of large charge / discharge currents. The sulfur molar fraction α is preferably 0.035 or more. On the other hand, if the sulfur molar fraction α exceeds 0.05, the ratio of the components actually capable of charging and discharging contained in the positive electrode active material decreases, thereby decreasing the discharge energy. The sulfur molar fraction α is preferably 0.040 or less.

[0018] The sulfur content in LMFP can be easily adjusted to within the above range, for example, by adding a certain amount of a sulfide source such as hydrogen sulfide, carbon disulfide, or lithium sulfide as an additive to the raw material in the LMFP production method described below.

[0019] In addition, the molar ratio of the total content of polyvalent metal ions to the phosphorus content of the LMFP particles (total amount of polyvalent metal ions / P content) is preferably 0.97 or more and 1.03 or less. Here, the total content of polyvalent metal ions means the total content of ions of transition metals and alkaline earth metals contained as manganese, iron, and other doping sources (hereinafter, these may be collectively referred to as polyvalent metal ions). By setting the molar ratio of the total content of polyvalent metal ions to 0.97 or more, valence matching can be almost completely achieved with the transfer of electrons due to charging and discharging, so that the discharge capacity can be further improved and the discharge energy can be further increased. On the other hand, by setting the molar ratio to 1.03 or less, the generation of impurity phases other than LMFP can be suppressed, so that the discharge capacity can be further improved and the discharge energy can be increased.

[0020] Here, the composition of LMFP can be determined by atomic absorption spectrometry for lithium, and ICP emission spectrometry for manganese, iron, phosphorus, and sulfur. The content of each element is measured to three decimal places and rounded off to the second decimal place. In addition, if the raw material feed ratio during LMFP production is known, the composition can be determined from that feed ratio.

[0021] The LMFP primary particles preferably have a carbon layer on the surface, and more preferably have a carbon layer uniformly over the entire surface. By having a carbon layer, it is possible to improve electronic conductivity uniformly over the entire positive electrode active material made of LMFP. The content of the carbon layer in the LMFP primary particles is preferably 1% by weight or more from the viewpoint of further improving electronic conductivity and increasing discharge energy. On the other hand, the content of the carbon layer in the LMFP primary particles is preferably 6% by weight or less from the viewpoint of suppressing a side reaction between the carbon layer and the LMFP and increasing discharge energy.

[0022] Here, the carbon layer content of the LMFP particles can be measured using, for example, a carbon / sulfur simultaneous quantitative analyzer EMIA-920V (manufactured by Horiba, Ltd.).

[0023] The volume resistivity ρ (Ω·cm) of the secondary particles of the LMFP in this invention is 10 2 ≦ρ≦10 6 As described above, LMFP has a stable olivine structure and is therefore a highly safe material. In order to further improve the safety of the positive electrode, it is preferable to reduce the current that flows when an abnormality occurs by setting the resistance of the positive electrode secondary particles to a certain value or higher. For this reason, the volume resistivity of the secondary particles of the LMFP in the present invention is set to 10 2 (Ω·cm) or more is preferable, and 10 3 (Ω·cm) or more is preferable. On the other hand, if the volume resistivity of the secondary particles of LMFP is 10 6(Ω·cm) or less, the discharge energy of the secondary particles of LMFP can be maintained higher. Here, the volume resistivity of the secondary particles of LMFP can be measured for the LMFP secondary particles in the positive electrode under a condition of 25 MPa using, for example, a powder resistivity measuring system MCP-PD51 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.). As a method for extracting the LMFP secondary particles from the positive electrode, for example, a method in which the mixture layer is peeled off from the current collector of the positive electrode, the binder is dissolved with an organic solvent such as N-methylpyrrolidinone, and the remaining LFMP secondary particles are dried, etc. can be mentioned. Furthermore, when a conductive assistant such as carbon black is contained, a method in which the carbon black having a low specific gravity is removed from the remaining solid by centrifugal separation after dissolving the binder, and the obtained LFMP secondary particles are dried, etc. can be mentioned. In addition, the volume resistivity of the LMFP secondary particles as a raw material in the production of the positive electrode may be measured in the same manner.

[0024] The volume resistivity of the secondary particles of the LMFP can be adjusted to a desired range by the ratio of manganese to iron, the primary or secondary particle size, the sulfur content, and, in the case of an LMFP having a carbon layer, the carbon layer content, the firing temperature, and other carbon coating conditions.

[0025] The secondary particle diameter of the LMFP is preferably 3 μm or more from the viewpoint of the handleability of the paste in the manufacturing method of the positive electrode described later. On the other hand, the secondary particle diameter of the LMFP is preferably 40 μm or less from the relationship with the thickness of the mixture layer described later. The secondary particle diameter of the LMFP refers to the arithmetic mean value of the particle diameter of the secondary particles, and can be measured using a scanning electron microscope. Specifically, the positive electrode is observed at a magnification of 3,000 times using a scanning electron microscope, and the secondary particle diameter of 100 randomly selected secondary particles is measured. The secondary particle diameter of the LMFP can be obtained by calculating the number average value. In addition, the secondary particle diameter of the LMFP as a raw material in manufacturing the positive electrode may be similarly measured using a scanning electron microscope.

[0026] The secondary particle size of LMFP can be easily adjusted to a desired range, for example, by using a spray dryer in the LMFP production method described below and changing the weight concentration of the LMFP aqueous dispersion, which is the raw material.

[0027] The crystallinity and particle shape of the LMFP primary particles were determined by the ratio of the peak intensity at 20° to the peak intensity at 29° obtained by X-ray diffraction, I 20 / I 29 , the ratio of the peak intensity at 35° to the peak intensity at 29° I 35 / I 29 It can be evaluated by: 20 / I 29 When I is 0.88 or more and 1.05 or less, it means that the LMFP primary particles are not highly oriented in the b-axis direction, and the particle shape is closer to a sphere than a plate. By making the particles closer to a spherical shape, the distortion of the crystal lattice caused by the insertion and removal of lithium ions during charging and discharging can be alleviated, and the discharge energy can be further improved even under conditions of large charge and discharge currents. In addition, I 35 / I 29 When the ratio is 1.05 or more and 1.20 or less, the crystal orientation of the LMFP primary particles is further decreased, the crystal orientation is more uniform, and the particle shape is closer to a sphere. Therefore, the distortion of the crystal lattice caused by the deintercalation and insertion of carrier ions during charging and discharging is alleviated, and the discharge energy under conditions of large charging and discharging currents can be further improved.

[0028] The peak intensity ratio can be determined by performing powder X-ray diffraction measurement on a powder sample of LMFP at a diffraction angle 2θ in the range of 10 degrees or more and 70 degrees or less, removing the background, reading the peak intensities, and calculating the ratio.

[0029] Also, I 20 / I 29 and I 35 / I 29 As a method for adjusting the amount of LMFP to fall within the above range, for example, a method for obtaining LMFP by a preferable production method described later can be mentioned.

[0030] The positive electrode of the present invention preferably has a mixture layer containing additives such as a binder and a conductive assistant together with the LMFP on a current collector such as aluminum foil. The LMFP is preferably contained as secondary particles.

[0031] Examples of the binder include polyvinylidene fluoride, styrene-butadiene rubber, etc. Two or more of these may be contained.

[0032] The content of the binder in the positive electrode mixture layer is preferably 0.3% by weight or more and 10% by weight or less. By making the content of the binder 0.3% by weight or more, the shape of the coating film can be easily maintained when the coating film is formed due to the binding effect of the binder. On the other hand, by making the content of the binder 10% by weight or less, an increase in the resistance in the positive electrode can be suppressed.

[0033] Examples of the conductive assistant include acetylene black, ketjen black, carbon fiber, carbon nanotubes, etc. Two or more of these may be contained.

[0034] The content of the conductive assistant in the mixture layer is preferably 0.3% by weight or more and 10% by weight or less. By making the content of the conductive assistant 0.3% by weight or more, the conductivity of the positive electrode can be improved and the electronic resistance can be reduced. On the other hand, by making the content of the conductive assistant 10% by weight or less, the inhibition of the movement of lithium ions by the conductive assistant can be suppressed, and the decrease in ion conductivity can be suppressed.

[0035] In order to increase the energy density of a lithium-ion secondary battery, it is preferable that the positive electrode mixture layer contains as high a proportion of the positive electrode active material as possible, and the LMFP secondary particle content in the positive electrode mixture layer is preferably 80% by weight or more, and more preferably 85% by weight or more.

[0036] The thickness of the positive electrode mixture layer is preferably 10 μm or more and 200 μm or less. By making the thickness of the mixture layer 10 μm or more, the ratio of the current collector in the positive electrode can be reduced, and the energy density can be further improved. On the other hand, by making the thickness of the mixture layer 200 μm or less, the charge / discharge reaction can be rapidly progressed throughout the mixture layer, and the high-speed charge / discharge characteristics can be improved.

[0037] The lithium ion secondary battery of the present invention preferably has a negative electrode, a separator, and an electrolyte in addition to the positive electrode. The shape of the battery may be, for example, a square type, a wound type, a laminate type, or the like, and may be appropriately selected according to the purpose of use. Materials constituting the negative electrode may include, for example, graphite, lithium titanate, silicon oxide, or the like. The separator and electrolyte may also be selected from any suitable materials.

[0038] Next, a method for producing the positive electrode of the present invention will be described.

[0039] The LMFP of the present invention can be obtained by any method such as a solid-phase method or a liquid-phase method, but the liquid-phase method is preferred in that the ratio of manganese and iron is within the range of the present invention and particles having an average particle size in the above-mentioned preferred range can be obtained more easily. In addition to water, it is also preferred to use an organic solvent in the liquid phase to refine the particle size to nanoparticles, and the solvent type is, for example, an alcohol solvent such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 2-propanol, 1,3-propanediol, or 1,4-butanediol, or dimethyl sulfoxide. In the synthesis process, pressure may be applied to enhance the crystallinity of the particles. The ratio of manganese and iron contained in the LMFP can be adjusted to a desired range by the charging ratio of the raw materials. In addition, in the synthesis of LMFP by the liquid-phase method, it is preferred to add a solution containing the remaining raw materials while stirring at high speed a solution containing a part of the raw materials, and heat to the synthesis temperature without pressurizing while maintaining the high-speed stirring state, and the peak intensity ratio I obtained by X-ray diffraction of LMFP is 100%. 20 / I 29and I 35 / I 29 can be adjusted to fall within the above-mentioned preferred range.

[0040] When LMFP primary particles are obtained by a liquid phase method, the average primary particle size can be adjusted to a desired range by, for example, conditions such as the mixing ratio of water and organic solvent in the solvent, the concentration of the synthesis solution, the synthesis temperature, etc. Typically, in order to increase the average particle size, it is effective to increase the proportion of water in the solvent, to increase the concentration of the synthesis solution, to increase the synthesis temperature, etc.

[0041] A preferred carbon coating method for forming a carbon layer on the LMFP obtained by the liquid phase method is to mix the LMFP primary particles or secondary particles with sugars and then bake them under an inert gas atmosphere. As the sugars, glucose and sucrose are preferred because they have a low ash content after baking. The baking temperature is preferably 500°C or higher and 800°C or lower.

[0042] In the method for producing the LMFP secondary particles in the present invention, a spray dryer is preferably used in order to narrow the particle size distribution of the resulting secondary particles as much as possible.

[0043] The positive electrode of the present invention can be obtained, for example, by applying a paste in which the above-mentioned LMFP secondary particles are dispersed in a dispersion medium onto a current collector, drying, and pressing to form a mixture layer. As a method for producing the paste, it is preferable to mix and knead the above-mentioned LMFP secondary particles, and further additives such as a conductive assistant, a binder, and a dispersion medium such as N-methylpyrrolidinone as necessary, and add water or a dispersion medium such as N-methylpyrrolidinone to adjust the viscosity. The solid content concentration of the paste can be appropriately selected depending on the application method. From the viewpoint of making the coating film thickness uniform, it is preferable to be 30% by weight or more and 80% by weight or less. Each material of the paste may be mixed at once, or in order to uniformly disperse each material in the paste, it may be added and mixed in order while repeating kneading. As a kneading device for the slurry, a planetary mixer or a thin film swirl type high-speed mixer is preferable in terms of being able to knead uniformly.

[0044] The lithium ion secondary battery of the present invention can be obtained, for example, by laminating the above-mentioned positive electrode with a negative electrode via a separator in a dry environment with a dew point of −50° C. or lower, and adding an electrolyte solution. EXAMPLES

[0045] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. First, the evaluation methods used in the examples will be described.

[0046] [Measurement A] Crystallite size and X-ray diffraction peak intensity ratio Powder samples consisting of LMFP secondary particles used in each Example and Comparative Example were subjected to powder X-ray diffraction measurement at a diffraction angle 2θ range of 10 degrees to 70 degrees using an X-ray diffractometer D8 ADVANCE manufactured by Bruker AXS Inc. Based on the obtained diffraction pattern, Rietveld analysis was performed using analysis software TOPAS manufactured by Bruker AXS Inc. to calculate the crystallite size of LMFP. The peak intensity ratio was obtained by removing the background (coefficient 1.77) using powder X-ray diffraction analysis software DIFFRAC.EVA manufactured by Bruker AXS Inc., reading the peak intensities, and calculating the ratio. The values ​​obtained by dividing the peak intensities at 20° and 35° by the peak intensity at 29° were respectively expressed as I 20 / I 29 , I 35 / I 29 It was decided.

[0047] [Measurement B] Chemical composition analysis 15 mg of powder sample made of LMFP secondary particles used in each Example and Comparative Example was thermally decomposed using perchloric acid and nitric acid, and the volume was adjusted to 100 mL using ultrapure water. For this solution, Li was measured by atomic absorption spectrometry, and Mn, Fe, P, and S were measured by ICP atomic emission spectrometry, and the respective contents in the sample were calculated and converted into atomic ratios.

[0048] [Measurement C] Discharge energy characteristics of positive electrode A 2032-type coin battery was produced by cutting the electrode plate produced in each Example and Comparative Example to a diameter of 15.9 mm to form a positive electrode, using a lithium foil cut to a diameter of 16.1 mm and a thickness of 0.2 mm to form a negative electrode, using "Setira" (registered trademark) as a separator, and using ethylene carbonate:diethyl carbonate = 3:7 (volume ratio) containing LiPF6 at a concentration of 1 M as an electrolyte.

[0049] The fabricated 2032-type coin battery was charged and discharged twice at a 0.1 C rate, followed by two consecutive charges and discharges at a 3 C rate, with a cutoff voltage of 2.5 V and a maximum charging voltage of 4.3 V. For each charge and discharge rate, the discharge energy was measured from the second discharge, and the energy density (Wh / kg) per unit weight of LMFP was calculated.

[0050] [Example 1] (Step 1: Preparation of LMFP secondary particles) 200g of dimethyl sulfoxide and 15g of carbon disulfide were added to 150g of pure water, and 390mmol of lithium hydroxide monohydrate was added. 120mmol of phosphoric acid was further added to the obtained solution using 85wt% phosphoric acid aqueous solution, and 96mmol of manganese(II) sulfate monohydrate and 24mmol of iron(II) sulfate heptahydrate were further added. The obtained solution was transferred to an autoclave and heated and held for 4 hours so that the temperature inside the container was maintained at 150°C. After heating, the supernatant of the solution was discarded, and lithium manganese iron phosphate was obtained as a precipitate. The obtained lithium manganese iron phosphate was washed with pure water, and the operation of removing the supernatant by centrifugation was repeated five times, and finally pure water was added again to obtain a dispersion. Next, glucose was added to the dispersion in an amount equal to 15wt% of the lithium manganese iron phosphate in the dispersion and dissolved, and then pure water was added to adjust the solid concentration of the dispersion to 50wt%, to obtain an LMFP dispersion.

[0051] The obtained LMFP dispersion was dried with hot air at 200°C using a spray dryer (MDL-050B, manufactured by Fujisaki Electric Co., Ltd.) to obtain secondary particles. The obtained secondary particles were heated at 700°C for 4 hours in a nitrogen atmosphere using a rotary kiln (desktop rotary kiln, manufactured by Takasago Industrial Co., Ltd.) to obtain carbon-coated LMFP secondary particles.

[0052] (Step 2: Preparation of electrode plate) Acetylene black (Li-400 manufactured by Denka Co., Ltd.) and binder (Kureha KF Polymer Co., Ltd. L#9305) were mixed, and the LMFP secondary particles obtained by the above method were added and kneaded in a mortar. At that time, the weight ratio of each material contained was LMFP secondary particles: acetylene black: binder was 90: 5: 5. Then, N-methylpyrrolidinone was added to adjust the solid content to 48 wt%, and a slurry-like electrode paste was obtained. N-methylpyrrolidinone was added until the obtained paste had fluidity, and it was treated for 30 seconds under stirring conditions of 40 m / sec using a thin film rotating type high-speed mixer ("Filmix" (registered trademark) 40-L type manufactured by Primix Corporation).

[0053] The obtained electrode paste was applied to an aluminum foil (thickness 18 μm) using a doctor blade (300 μm), dried at 80° C. for 30 minutes, and then pressed to prepare an electrode plate.

[0054] [Example 2] An electrode plate was prepared in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 20 g, the amount of lithium hydroxide monohydrate added was 400 mmol, the amount of manganese (II) sulfate monohydrate added was 104 mmol, and the amount of iron (II) sulfate heptahydrate added was 26 mmol.

[0055] [Example 3] An electrode plate was prepared in the same manner as in Example 1, except that the amount of manganese (II) sulfate monohydrate added in step 1 was 88 mmol, and the amount of iron (II) sulfate heptahydrate added was 22 mmol.

[0056] [Example 4] An electrode plate was produced in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 10 g.

[0057] [Example 5] An electrode plate was produced in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 25 g.

[0058] [Example 6] An electrode plate was prepared in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 25 g, the amount of lithium hydroxide monohydrate added was 400 mmol, the amount of manganese (II) sulfate monohydrate added was 84 mmol, the amount of iron (II) sulfate heptahydrate added was 36 mmol, and the amount of glucose added to the LMFP dispersion was the same as 10% by weight of lithium manganese iron phosphate.

[0059] [Example 7] (Step 1: Preparation of LMFP secondary particles) After dissolving 65 mmol of lithium hydroxide monohydrate and 5 mmol of lithium sulfide in 16 g of pure water, 104 g of diethylene glycol was added to prepare a lithium hydroxide-lithium sulfide / diethylene glycol aqueous solution. On the other hand, 20 mmol of phosphoric acid (85% aqueous solution), 16 mmol of manganese (II) sulfate monohydrate, and 4 mmol of iron (II) sulfate heptahydrate were dissolved in 10 g of pure water to prepare a manganese sulfate-iron sulfate / phosphoric acid aqueous solution. The lithium hydroxide-lithium sulfide / diethylene glycol aqueous solution was stirred at 2000 rpm using a homodisper (Primix Corporation, Homodisper 2.5 type), and the manganese sulfate-iron sulfate / phosphoric acid aqueous solution was added to obtain an LMFP precursor solution. The obtained LMFP precursor solution was heated to 110 °C and held for 2 hours to obtain LMFP particles. The obtained particles were washed by adding pure water and repeatedly removing the solvent using a centrifuge. The same operation was repeated to obtain a dispersion containing 10 g of washed LMFP particles. Next, glucose in an amount equal to 15% by weight of LMFP was added to the dispersion, and then pure water was added and stirred to adjust the solid content of the dispersion to 50% by weight, thereby obtaining an LMFP dispersion.

[0060] The obtained LMFP dispersion was dried with hot air at 200°C using a spray dryer (MDL-050B, manufactured by Fujisaki Electric Co., Ltd.) to obtain secondary particles. The obtained secondary particles were heated at 700°C for 4 hours in a nitrogen atmosphere using a rotary kiln (desktop rotary kiln, manufactured by Takasago Industrial Co., Ltd.) to obtain carbon-coated LMFP secondary particles.

[0061] An electrode plate was produced in the same manner as in Example 1 (step 2) using the obtained carbon-coated LMFP secondary particles.

[0062] [Comparative Example 1] An electrode plate was prepared in the same manner as in Example 1, except that the amount of water added in step 1 was 120 g and the amount of carbon disulfide added was 20 g.

[0063] [Comparative Example 2] An electrode plate was prepared in the same manner as in Example 1, except that the amount of lithium hydroxide monohydrate added in step 1 was 400 mmol, the amount of manganese (II) sulfate monohydrate added was 36 mmol, and the amount of iron (II) sulfate heptahydrate added was 84 mmol.

[0064] [Comparative Example 3] An electrode plate was prepared in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 20 g and the amount of lithium hydroxide monohydrate added was 360 mmol.

[0065] [Comparative Example 4] An electrode plate was prepared in the same manner as in Example 1, except that the amount of lithium hydroxide monohydrate added in step 1 was 420 mmol.

[0066] [Comparative Example 5] An electrode plate was produced in the same manner as in Example 1, except that in step 1, carbon disulfide was not added.

[0067] [Comparative Example 6] An electrode plate was produced in the same manner as in Example 1, except that the amount of carbon disulfide added in step 1 was 40 g.

[0068] The evaluation results of each of the examples and comparative examples are shown in Table 1.

[0069] [Table 1]

Claims

1. A positive electrode for a lithium ion secondary battery containing, as an active material, olivine-type lithium manganese iron phosphate particles containing elemental sulfur inside the particles, A positive electrode for a lithium ion secondary battery, wherein the crystallite size of the olivine-type lithium manganese iron phosphate is less than 60 nm, the molar fraction of the manganese content to the total content of manganese and iron (Mn content / (Mn+Fe) content) is 0.5 or more and less than 1.0, the molar ratio of the lithium content to the phosphorus content (Li content / P content) is 1.05 or more and 1.10 or less, and the molar fraction of sulfur in the olivine-type lithium manganese iron phosphate (S content / lithium manganese iron phosphate content) is 0.03 or more and 0.05 or less.

2. 2. The positive electrode for a lithium ion secondary battery according to claim 1, wherein the molar ratio of the total content of polyvalent metal ions to the phosphorus content of the olivine-type lithium manganese iron phosphate (total amount of polyvalent metal ions / P content) is 0.97 or more and 1.03 or less.

3. 3. The positive electrode for a lithium ion secondary battery in accordance with claim 1, wherein a molar fraction of sulfur in the olivine-type lithium manganese iron phosphate is 0.035 or more and 0.040 or less.

4. The secondary particles of the olivine-type lithium manganese iron phosphate have a volume resistivity of 10 2 Ω・cm or more 10 6 The positive electrode for lithium ion secondary batteries according to any one of claims 1 to 3, wherein the resistance is Ω cm or less.

5. The ratio I of the peak intensity at 20° to the peak intensity at 29° obtained by X-ray diffraction of the olivine-type lithium manganese iron phosphate 20 / I 29 is 0.88 or more and 1.05 or less, and the ratio I 35 / I 29 The positive electrode for a lithium ion secondary battery according to any one of claims 1 to 4, wherein is 1.05 or more and 1.20 or less.

6. A lithium ion secondary battery using the positive electrode for lithium ion secondary batteries according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Electrode active substance, electrode material, method of manufacturing the same, electrode, and battery

    JP2010161038A

  • Lithium secondary battery and positive electrode for lithium secondary battery

    JP2011076820A

  • Positive electrode active material for nonaqueous electrolyte battery, positive electrode for nonaqueous electrolyte battery, and nonaqueous electrolyte battery

    JP2012104290A

  • Lithium iron phosphate having a carbon-coated olivine crystal structure, and lithium secondary batteries using it.

    JP2013528557A

  • Mixed cathode materials

    JP2014524133A